Cultural sensemaking of corporate social responsibility: A dyadic view of Russian–Finnish business relationships - Ivanova-Gongne Maria; Torkkeli Lasse; Hannibal Martin; Uzhegova Maria; Barner-Rasmussen Wilhelm; Dziubaniuk Olga; Kulkov Ignat (Elsevier, 2022)
International Management (IM) needs a better understanding of how managers of small and medium-sized enterprises (SMEs) make sense of cultural differences in international business relationships, especially regarding corporate social responsibility (CSR) in relationships between firms from emerging and developed countries. We address this lacuna by uncovering how dyads of Russian and Finnish SME managers, engaged in mutual international business relationships, construct their understanding of CSR. The findings indicate that conceptualizations of CSR are embedded both in SME managers' cultural backgrounds and in the contextual environment. This extends previous research on the role of CSR in IM and respond to calls to study the microfoundations of CSR and internationalization, adding to the sparse knowledge of CSR in cross-cultural SME settings.